Age threshold for moderate and severe periodontitis among Korean adults without diabetes mellitus, hypertension, metabolic syndrome, and/or obesity. Issue 33 (August 2017) - Han, Kyungdo; Park, Jun-Beom
Abstract : Abstract: The purpose of this study is to determine an appropriate age threshold at which to recommend the evaluation of moderate and severe periodontitis among Korean adults. This study involved a cross-sectional analysis using data from the Korean National Health and Nutrition Examination Survey from 2012 to 2014. Incidence rates of periodontitis with the 95% confidence interval (CI) were evaluated. The predictive accuracy of age for periodontitis was determined by calculating the area under curve (AUC) on the basis of the receiver operating characteristic (ROC) curve. The cutoff value of age was 43 years in men having periodontitis with an AUC of 0.70 with 95% CI of 0.69 to 0.72. The AUC was 0.72 (95% CI: 0.70–0.73), and the cutoff value of age (49 years) was identified for the moderate periodontitis in women. The cutoff values for age with AUCs and 95% CI for individuals with periodontitis were 46 years (0.72 [0.71–0.73]), 43 years (0.73 [0.72, 0.74]), 45 years (0.71 [0.70, 0.72]), 43 years (0.73 [0.72, 0.74]), and 45 years (0.74 [0.72, 0.75]) for no obesity, no abdominal obesity, no diabetes mellitus, no hypertension, and no metabolic syndrome groups, respectively. This study proposed the guideline for the appropriate age threshold at which to recommend the evaluation of moderate and severe periodontitis for the general population and additionally added the guideline for the individuals without systemic disease including diabetes mellitus, hypertension, metabolic syndrome, and obesity. This study suggests that the participants with certain age may be recommended for the regular periodontal evaluation. Abstract : Supplemental Digital Content is available in the text